AI-Powered Libraries: Comparative Insights for an Adaptive Repository - Talasbek, A.; Bogdanchikov, A.; Meraliyev, M.; Amirkumar, M; Zhaparov, M. (Karagandy University of the name of academician E.A. Buketov, 2025)
This paper examines how academic staff access and use e-books, and what features they expect from a future digital library platform. Based on survey results, the study reveals that most respondents rely on informal sources, while official databases are used less frequently. At the same time, there is strong demand for key functionalities such as access to a wide collection of e-books, quiz generation, personalized recommendations, and tools for tracking student performance. In addition, the paper provides a comparative review of existing platforms—Perlego, QuizBot, Bookmate, Khan Academy, and Scopus—highlighting both their strengths and limitations, particularly with respect to language support and integration. Taken together, the survey findings and platform analysis underscore the need for a unified adaptive platform that connects publishers, libraries, and users, thereby enhancing accessibility, interoperability, and effectiveness in digital learning.
Keywords: E-books; digital library platforms; adaptive learning; personalization; interoperability; accessibility